Identity Crisis As A Threat Among Indonesian Young Generations - Elisha Samantha Dewi Manurung; Faukha Ilmania Salsabila; Putu Tanisya Putri Wirawan; Nadila Dwi Anggraini; Moses Glorino Rumambo Pandin (Populasi, 2022)
In living life as a part of a nation and state, people sometimes feel confused about what is more important between the country and the state, and they sometimes even underestimate the two. The state is an organization of power from the fellowship of human life, while the nation refers to the harmony of human life. A country must have its own national identity that differs from other countries since the national identity of a nation shows its personality. This study aims to observe the condition of national identity among the young generation and attempts to overcome the threat of a national identity crisis. The method used in this study is descriptive analysis with data collection techniques by conducting surveys and interviews. The population in this study consist of private high school and university students. In this study, the sample used was 160 people aged 15-20 years. The results indicated that the young generation is at a critical stage of national identity. It was caused by their inabilities to wisely use technology and a lack of sense of nationalism as well as love for their homeland. This study found many, lacks as it is seen in the students who still used their respective regional languages because they were vulnerable to any trigger according to the perspectives, principles, and goals of each student. Furthermore, based on research results, teenagers tend to be more fond of foreign cultures and consider Indonesian cultural heritage outdated. For this reason, it is necessary to instill a sense of pride and love for the homeland among young people so that the culture remains sustainable. The researchers suggest the Indonesian people, especially the young generation to have more concern about the national identity of the Indonesian nation since it is essential to increase the horizon of knowledge, and it is also hoped that the young generation can apply an understanding on national identity and be able to implement the points of Pancasila in life nation, society, and state.